Female corporate leadership in Latin America and the Caribbean region: Representation and firm-level outcomes. Issue 6 (4th September 2017) - Flabbi, Luca; Piras, Claudia; Abrahams, Scott
Abstract : Purpose: Despite gender parity in the general working population, the higher up one looks in ranks within the firm the fewer women one finds. This under-representation of women in top positions at firms is purportedly even more acute in Latin America and the Caribbean (LAC). LAC is a large and increasingly important region of the world where women are well-represented in the workforce and are comparatively better educated than men. Documenting if this resource is utilized at full potential is therefore of crucial importance. The purpose of this paper is to document the level and impact of female representation at the executive level in the region, as no systematic study exists on this topic. Design/methodology/approach: The authors collect an original database of publicly listed companies to determine prevailing gender ratios among board members and executives in LAC region. The authors then estimate whether companies with women board members are more likely to appoint women executives. Finally, the authors estimate whether measures of female leadership at the firm are correlated with company performance. Findings: The authors find that women are as under-represented in LAC as in the USA, but much less so in the Caribbean. The authors find that companies with women board members are more likely to appoint women executives in LAC. The authors find that measures of female leadership at the firm are correlated with company performance but only regarding board membership and only when the proportion of women on the board is greater than 30 percent. Again composition effects are important. Overall, the authors conclude that the LAC region exhibits empirical regularities about under-representation of women in leadership positions at the firm that are very similar to those found for high-income countries in Europe and North America. Originality/value: The authors are the first and so far unique systematic study exists able to document the level and impact of female representation at the executive level in the region.